Walking with Bhekizizwe Peterson: The shadows and afterlives of exile - Nkomo, Nkululeko (PINS-Psychology in Society, 2024)
Zwelidumile “Dumile” Feni’s affecting journey unfolds as he flees South Africa in 1968, seeking political exile in England until 1978, and subsequently relocating to the United States, where he painted and sculpted until his passing in 1991. The spectral echoes of his life find resonance in his daughter’s narrative within Ramadan Suleman and Bhekizizwe Peterson’s film ʻZwelidumile’. This article argues that we must situate this documentary in context by examining the emotional toll and narrative accounts of the longer history of displacement brought about by colonialism and apartheid. The analysis begins by listening to the haunting signs within the documentary, revealing three moving themes. The first theme peels back the layers of secrecy, spotlighting the revelation of Marriam’s biological father – drawing attention to the spectral and melancholic imbrication. The narrative then explores Feni’s life in exile, examining his deliberate silence on familial matters in South Africa. The last of the three themes looks into Marriam’s acknowledged but bewildering loss, exploring its implications for a sense of self and continuity. Zwelidumile exemplifies Bhekizizwe Peterson’s steadfast commitment to shedding light on the complex nuances of the black experience and emphasising narrative’s vital role as an essential component of what makes us human.